(untitled) (Research, Society and Development, 2021)
In the neoliberal capitalist context, the fear of the state’s helplessness, as a reflection of the permanent and multi-scale processes of social exclusion, penetrates the development of relationships, solidifying them into extracts. In this stratification process, fear builds barriers in which an individual, the otherness, is a synonym of threat and danger: a someone or something to be avoided. As a result, there is an intensification of the polarization between classes, beliefs, ethnicities, ideologies. Therefore, it creates a uniform structure of interactions, based on the assumption that differences must be repressed or excluded. This social practice favors the emergence of anempathic, immune and, destructively, self-immune individuals. This work proposes the understanding of the urban social context of the city of São Paulo through a bibliographical review and, from this, analyzes, as an object of study, how the 9 de julho Occupation acts contrary to these enclaves. Territorialized in the city, often through urban occupations that seek to position themselves in a civil and urban way, they are capable of local transmutations on a world level; here, more specifically, the change of the scenery in São Paulo.